Rang & Dale's pharmacology - Ritter, James M.; Flower, Rod; Henderson, Graeme; Loke, Yoon Kong; MacEwan, David; Robinson, Emma; Fullerton, James (Elsevier, 2024)
This essential book is recommended as the first-choice undergraduate text for science and medical students and junior doctors and will also be useful for students in other professional disciplines such as pharmacy, veterinary medicine and nursing. Comprehensive information on drug mechanisms, basic physiology and biochemistry, and underlying pathophysiology of disease - suitable for students from many disciplines Clear figures to aid understanding, including data figures as well as mechanistic diagrams, Key points box summaries, clinical boxes and colour-coded chapters help to master difficult concepts Emphasis on therapeutic drugs to help apply theory to practice Over 150 questions and 12 clinical cases to test your knowledge An enhanced eBook version is included with purchase.